Surface settlement modelling using neural network - Chen, Rongxing (Nanyang Technological University, 2020)
With the development of society, the utilization rate of underground space is getting higher and higher. Tunnel projects are gradually increasing. But settlement is the most common problem in tunnel engineering. Many scholars have conducted research on this issue, and they have developed many methods for predicting the settlement. But these methods have some shortcomings, that is, they are too complicated, and the accuracy of prediction is not high.